الأحاديث الواردة في النهي عن الإقامة في بلاد المشركين - ابراهيمي, محمد العيد; رومان, محمد الطاهر (University of Eloued-جامعة الوادي, 2022)
"الحمد لله رب العالمين والصلاة والسلام على أشرف الأنبياء والمرسلين وعلى أله وصحبه أجمعين. إن موضوع بحثنا هو: الأحاديث الواردة في النهي عن الإقامة في بلاد المشركين، وقد بدأنا بمقدمة بينا فيها الإشكالية المتعلقة بالبحث، وذكرنا فيها أهمية الموضوع وأسباب اختياره، وذكرنا أهم الأهداف المرجو تحقيقها ثم عرجنا على الدراسات السابقة وبينا المنهج المتبع في البحث وذكرنا فيها الخطة. وقد تضمنت الخطة مبحثين: المبحث الأول كان تحت عنوان التعريف بمصطلحات الدراسة وموقف العلماء من الإقامة في بلاد المشركين، وقسمناه إلى مطلبين: المطلب الأول: التعريف بمصطلحات الدراسة، وأما المطلب الثاني موقف العلماء من الإقامة في بلاد المشركين، وأما المبحث الثاني: كان بعنوان الأحاديث الواردة: (في الهجر من بلاد المشركين – وفي النهي عن الإقامة ببلاد المشركين – في النهي عن مساكنة المشركين)، وقد تضمن هذا المبحث ثلاث مطالب، المطلب الأول: ما ورد في الهجرة من بلاد المشركين، المطلب الثاني: ما ورد في النهي عن الإقامة ببلاد المشركين، المطلب الثالث: ما ورد في النهي عن مساكنة المشركين، حيث قمنا في كل مطلب بذكر الأحاديث وتخريجها وذكر حكم علماء الحديث عليها. وأنهينا الرسالة بخاتمة ضمنا فيها أهم النتائج التي قادنا إليها البحث.""Praise be to God, Lord of the humans, and prayers and peace be upon the most honorable of the prophets and messengers, and upon all his family and companions. The topic of our research is: the hadiths mentioned in the prohibition of residing in the countries of the polytheists, and we started with an introduction in which we clarified the problem related to the research, and mentioned in it the importance of the topic and the reasons for choosing it, and mentioned the most important goals to be achieved, then we referred to the previous studies and explained the approach followed in the research and mentioned the plan. The plan included two sections: the first topic was under the title “Introducing the terminology of the study and the position of scholars regarding residency in the lands of the polytheists. contained: (in emigration from the lands of the polytheists - and in the prohibition of residence in the lands of the polytheists - in the prohibition of cohabitation with the polytheists). In the lands of the polytheists, the third requirement: What is stated in the prohibition of cohabitation with the polytheists, where in each demand we mentioned the hadiths and extracted them and mentioned the ruling of the hadith scholars on them. We ended the thesis with a conclusion in which we included the most important results that the research led us to."
مذكرة ماستر
Keywords: الاحاديث.النهي.بلاد المشركين; prohibition.conversations.metholic country